Bhutan Development Update, April 2021 - World Bank (World Bank, Washington, DC, 2021)
Although Bhutan has made progress in recent years, notably by initiating the development of a domestic e-commerce ecosystem, gaps still remain. The Royal Government of Bhutan (RGoB) has prioritized information and communications technology (ICT) development to promote the vision of ‘an ICT-enabled, knowledge society as a foundation for Gross National Happiness.’ Initiatives, such as the Digital DrukYul flagship program, the guidelines on e-commerce and the e-commerce Policy Framework, aim to increase Bhutan’s digitalization and participation in e-commerce. Yet, constraints in the e-trade environment, such as limited Internet connectivity, high costs of payment transactions, an incomplete regulatory infrastructure, and high trade facilitation and logistics costs, still hold Bhutan back, resulting in low levels of e-trade participation at present. The special focus section assesses the main regulatory and trade facilitation priorities for digital trade in Bhutan and makes concrete proposals to develop the country’s e-trade framework. The development of Bhutan’s digital economy and e-trade is contingent on a number of complementary factors including reliable Internet connectivity, mobile and computer penetration, digital literacy, availability of efficient logistical and payment systems, and relevant infrastructure to facilitate those factors. E-trade in goods and services also requires supporting policies in areas such as data protection, cyber security, consumer protection, competition law and the recognition of e-signatures and electronic transactions, which are the basic building blocks of all business online.